Development of smart electric double burner stove powered by Photooltaic energy - Firuz, Sanjida; Siddiqua, Samira; Nur, Bareed Mohammad; Jawwad, Raonaq (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.